2004
DOI: 10.1152/ajpheart.00102.2003
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in gene coding for ACE determines different development of myocardial fibrosis in rats

Abstract: .-In humans, the effect of angiotensinconverting enzyme (ACE) gene polymorphisms in cardiovascular disease is still controversial. In the rat, a microsatellite marker in the ACE gene allows differentiation of the ACE gene polymorphism among strains with different ACE levels. We tested the hypothesis that this ACE gene polymorphism determines the extent of cardiac fibrosis induced by isoproterenol (Iso) in the rat. We used a male F2 generation (homozygous LL and BB ACE genotypes determined by polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
11

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 47 publications
1
37
0
11
Order By: Relevance
“…The difference between WU-B and WU-L rats was statistically significant (p \ 0.001), with more staining present in WU-B lines (a) cardiovascular tissue but with corresponding results. In follow-up studies between these two strains by Ocaranza et al (2004), higher left ventricular ACE activity was reported in connection to B homozygous ACE allele.…”
Section: Described This Polymorphism In Inbred Brownmentioning
confidence: 92%
See 1 more Smart Citation
“…The difference between WU-B and WU-L rats was statistically significant (p \ 0.001), with more staining present in WU-B lines (a) cardiovascular tissue but with corresponding results. In follow-up studies between these two strains by Ocaranza et al (2004), higher left ventricular ACE activity was reported in connection to B homozygous ACE allele.…”
Section: Described This Polymorphism In Inbred Brownmentioning
confidence: 92%
“…Challah et al (1998) demonstrated that ACE activity in cultured vascular cells and in neointima formation in the carotid artery after balloon injury was influenced by ACE levels. Moreover, Ocaranza et al (2002Ocaranza et al ( , 2004 showed that there is an enhanced hypertensive response and more fibrosis in response to myocardial infarction in the Brown Norway rat with higher ACE levels. When studying the effect of the B and L alleles and their difference in ACE expression on the phenotype, it is important to realize that the Brown Norway and Lou rat strains have completely different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Además, la sobreexpresión de ECA2 regresó la fibrosis cardíaca en el modelo de HTA dependiente de Ang II, siendo la regresión de la fibrosis cardíaca mayor en las ratas LL AdECA2 respecto de las ratas BN. El modelo de ratas homocigotas LL y BN ha sido ampliamente utilizado en investigaciones previas del laboratorio 14,15,16 describiendo que en condiciones basales, las ratas BN presentan mayores niveles de ECA, renina y Ang II pero baja actividad de NEP y Ang-(1-7) 13,14 . En cambio, las ratas LL presentan características opuestas.…”
Section: Los Resultados Se Presentan Como Promedio ± Sem Abreviacionunclassified
“…En cambio, las ratas LL presentan características opuestas. Por otra parte, el pinzamiento de la arteria renal izquierda (modelo Goldblatt, GB, 2K-1C) genera mayor HTA en las ratas BN que las LL [15] y mayor desarrollo de fibrosis miocárdica inducida por isoproterenol 16 , lo cual explica que la regresión de la fibrosis haya sido mayor en las ratas LL tratadas con AdECA2. Las principales limitaciones de este estudio es que desconocemos a la fecha si el efecto terapéutico de la ECA2 en la disminución de la HTA y la regresión de la hipertrofia y la fibrosis cardíaca se relaciona con mejoría de la función ventricular.…”
Section: Los Resultados Se Presentan Como Promedio ± Sem Abreviacionunclassified
See 1 more Smart Citation